Digital Marketing for the Cultural and Tourism Industry in the Three Eastern Provinces Research on Development Impact - Gan, Chanyu (International Journal of Global Economics and Management, 2024)
In 2023, the General Office of the State Council issued several measures to unleash the potential of tourism consumption and promote high-quality development of the tourism industry. Local governments actively responded to national policies and promoted the development of cultural and tourism economy. The three eastern provinces are tourist destinations every winter, and their unique scenery and cultural sentiment make the Northeast region stand out during holidays. This winter, Harbin’s ice and snow tourism has become popular, even sparking a competition frenzy among other regions in Northeast China and even the National Bureau of Culture and Tourism. This paper uses the SWOT model and PEST model to analyze Northeast China’s natural and human resources, so as to study the help and advantages of digital marketing for its innovation and development, the lessons learned will help to provide a powerful marketing tool and channel for the cultural tourism industry, and promote the creative transformation of the current stage in the development of cultural tourism in Northeast China and throughout the country.